CULTURAL IDENTITY AND TRANSFORMATIVE SCULPTURE: A REFLECTION ON THE ARTISTIC TRAJECTORY OF AZWAN ABDUL KARIM - Abdul Karim, Azwan; Ibrahim, Zukeri; Zali, Abdul Aziz Zalay (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This practice-based research investigates the artistic trajectory of Azwan Abdul Karim @ Wan de Real, with a focus on the development of his INTRANS methodology of transformative sculpture. The study explores how childhood engagements with handmade toys and global popular culture, particularly 1980s animation and action figures, shaped his creative identity and informed his sculptural practice. The research employs studio experimentation, documentation, and critical self-reflection as primary methods, supported by empirical data such as process notes, collaborative projects with artisans, and visual analysis of artworks. The theoretical framework draws on Stuart Hall’s concept of cultural identity as a dynamic process and Homi Bhabha’s notion of hybridity and the third space, applied to interpret how Azwan’s sculptures reconfigure global influences into locally resonant forms. Findings demonstrate that Azwan’s INTRANS sculptures establish a new paradigm of modular, interactive, and culturally hybrid sculpture in Malaysia. This contribution expands the discourse of Malaysian contemporary art by integrating technological transformation with cultural identity, positioning local practice within global creative industries and offering a model for how Malaysian art can negotiate global popular culture while retaining local specificity.